Plasma C-Reactive Protein and Endothelin-1 Level in Patients with Chronic Obstructive Pulmonary Disease and Pulmonary Hypertension - Kwon, Yong Soo (The Korean Academy of Medical Sciences, 2010)
Pulmonary hypertension is a frequent complication of chronic obstructive pulmonary disease (COPD) and associated with a worse survival and increased risk of hospitalization for exacerbation of COPD. However, little information exists regarding the potential role of systemic inflammation in pulmonary hypertension of COPD. The purpose of the present study was to investigate the degree of C-reactive protein (CRP) and endothelin-1 (ET-1) levels in COPD patient with and without pulmonary hypertension. The levels of CRP and ET-1 were investigated in 58 COPD patient with pulmonary hypertension and 50 patients without pulmonary hypertension. Pulmonary hypertension was defined as a systolic pulmonary artery pressure (Ppa) ≥35 mmHg assessed by Doppler echocardiography. Plasma CRP and ET-1 levels were significantly higher in patients with pulmonary hypertension than in patients without hypertension. There were significant positive correlations between the plasma ET-1 level and CRP level in the whole study groups. For COPD patients, systolic Ppa correlated significantly with plasma CRP levels and plasma ET-1 levels. These findings support a possibility that CRP and ET-1 correlate to pulmonary hypertension in COPD patients.